2019
DOI: 10.3390/nu11030696
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mineral and Trace Element Supplementation in Exercise and Athletic Performance: A Systematic Review

Abstract: Minerals and trace elements (MTEs) are micronutrients involved in hundreds of biological processes. Deficiency in MTEs can negatively affect athletic performance. Approximately 50% of athletes have reported consuming some form of micronutrient supplement; however, there is limited data confirming their efficacy for improving performance. The aim of this study was to systematically review the role of MTEs in exercise and athletic performance. Six electronic databases and grey literature sources (MEDLINE; EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 204 publications
(330 reference statements)
1
79
1
5
Order By: Relevance
“…The concentration of mineral elements is usually under strict homeostatic control; however, physical activity alters this mechanism and brings changes in their serum levels [1][2][3][4]. Some studies report on the mineral concentrations in plasma, serum and urine.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of mineral elements is usually under strict homeostatic control; however, physical activity alters this mechanism and brings changes in their serum levels [1][2][3][4]. Some studies report on the mineral concentrations in plasma, serum and urine.…”
Section: Introductionmentioning
confidence: 99%
“…Minerals, also known as macrominerals or micronutrients, are inorganic elements which generally occur in large quantities, while trace elements or microminerals normally are present only in small amounts in organisms. Calcium, phosphorus, chloride, magnesium, phosphorus, potassium, sodium, and chloride are the elements playing vital roles in the body [82]. They regulate the proper composition and function of the body fluids, tissue, bone, teeth, muscles and nerves.…”
Section: Minerals and Trace Elementsmentioning
confidence: 99%
“…Essential trace elements required in smaller amounts by animals and plants are iron, zinc, copper, nickel, molybdenum, manganese, selenium, iodine, and others. These elements are involved in vital enzymatic reactions by acting as cofactors or by stabilizing cellular structures [82]. Based on their involvement in hundreds of biological processes, inadequate mineral and trace element intake can result in severe health conditions that can affect nearly all organs and tissues.…”
Section: Minerals and Trace Elementsmentioning
confidence: 99%
“…Omega 3 fatty acids play a fundamental role in reducing physiological inflammation through resolvins, and its utility for muscle damage and recovery in sports has been widely demonstrated [38]. Approximately 50% of athletes have reported consuming some form of micronutrient supplement; however, there is limited data confirming their efficacy for improving performance [39]. Mohiuddin, 2019 reported myocardial infarction, myocardial hypertrophy, hypertension, mood disorders, aggressive behavior, dependence syndrome, or cognitive effects with anabolic steroids.…”
Section: Introductionmentioning
confidence: 99%
“…Both Maciejewska-Skrendo and Cao et.al, 2019 suggested that Peroxisome proliferator-activated receptor delta (PPARD) gene is associated with dynamic balance performance of human being [50,51]. Iron and Magnesium supplementation have the best quality evidence for improvements to markers and outcomes related to exercise capacity and athletic performance [39], [52,53]. The use of creatine supplementation is still controversial.…”
Section: Introductionmentioning
confidence: 99%